The Parkinson's Disease Genome‐Wide Association Study Locus Browser. Issue 11 (31st August 2020) - Grenn, Francis P.; Kim, Jonggeol J.; Makarious, Mary B.; Iwaki, Hirotaka; Illarionova, Anastasia; Brolin, Kajsa; Kluss, Jillian H.; Schumacher‐Schuh, Artur F.; Leonard, Hampton; Faghri, Faraz; Billingsley, Kimberley; Krohn, Lynne; et al.
Abstract: Background: Parkinson's disease (PD) is a neurodegenerative disease with an often complex component identifiable by genome‐wide association studies. The most recent large‐scale PD genome‐wide association studies have identified more than 90 independent risk variants for PD risk and progression across more than 80 genomic regions. One major challenge in current genomics is the identification of the causal gene(s) and variant(s) at each genome‐wide association study locus. The objective of the current study was to create a tool that would display data for relevant PD risk loci and provide guidance with the prioritization of causal genes and potential mechanisms at each locus. Methods: We included all significant genome‐wide signals from multiple recent PD genome‐wide association studies including themost recent PD risk genome‐wide association study, age‐at‐onset genome‐wide association study, progression genome‐wide association study, and Asian population PD risk genome‐wide association study. We gathered data for all genes 1 Mb up and downstream of each variant to allow users to assess which gene(s) are most associated with the variant of interest based on a set of self‐ranked criteria. Multiple databases were queried for each gene to collect additional causal data. Results: We created a PD genome‐wide association study browser tool (https://pdgenetics.shinyapps.io/GWASBrowser/ ) to assist the PD research community with the prioritization of genes for follow‐up functional studies to identify potential therapeutic targets. Conclusions: Our PD genome‐wide association study browser tool provides users with a useful method of identifying potential causal genes at all known PD risk loci from large‐scale PD genome‐wide association studies. We plan to update this tool with new relevant data as sample sizes increase and new PD risk loci are discovered. © 2020 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. This article has been contributed to by US Government employees and their work is in the public domain in the USA.